Towards Rational Designing of Efficient Sensitizers Based on Thiophene and Infrared Dyes for Dye-Sensitized Solar Cells. (2nd January 2014) - Irfan, Ahmad; Al-Sehemi, Abdullah G.; Muhammad, Shabbir
Abstract : Geometries, electronic properties, and absorption spectra of the dyes which are a combination of thiophene based dye (THPD) and IR dyes (covering IR region; TIRBD1-TIRBD3) were performed using density functional theory (DFT) and time dependent density functional theory (TD-DFT), respectively. Different electron donating groups, electron withdrawing groups, and IR dyes have been substituted on THPD to enhance the efficiency. The bond lengths of new designed dyes are almost the same. The lowest unoccupied molecular orbital energies of designed dyes are above the conduction band of TiO2 and the highest occupied molecular orbital energies are below the redox couple revealing that TIRBD1-TIRBD3 would be better sensitizers for dye-sensitized solar cells. The broad spectra and low energy gap also showed that designed materials would be efficient sensitizers.